Of Birds and Breastfeeding: Augustine and Feminist Concerns about Kenosis - Kantzer Komline, Han-Luen (2025)
The doctrine of kenosis has kept a low profile in studies of the early church. Yet the biblical idea that Christ “emptied himself” was taken up not only by proponents of kenoticism in the nineteenth century, but also—inevitably—by early Christian thinkers as they interpreted Philippians 2:5-11, a crucial passage about the identity and spirit of Jesus Christ. Augustine, for example, references kenosis repeatedly across his writings. The notion of kenosis has also been a tenacious thread in the tapestry of feminist theological reflections over the last twenty years. This article weaves these strands together, arguing that three emphases of Augustine's account help to address concerns that feminist theologians have raised: his explication of kenosis as utterly unique and only analogically imitable; his description of kenosis as always additive; and his characterization of kenosis as an irresolvable paradox. This essay develops Augustine's emphases in conversation with recent feminist scholarship—drawing, along the way, on his surprising appeal to the behavior of mother birds and maternal breastfeeding—to suggest some new vantage points for appreciating how the Christian doctrine of kenosis can promote flourishing, for the subject as well as the object of self-giving love.